PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN STYROBON TERHADAP KREATIVITAS BERPIKIR DAN HASIL BELAJAR KOGNITIF - Silvia Rahmawati; Agus Kamaludin (Pendidikan Kimia Unimus, 2019)
This research aimed to examine the effect of the use of Styrobon learning media on the creative thinking skills and cognitive learning outcomes of 12th grade students on the subject of functional group in chemistry. The type of this research was Quasi Experiment by which the research design was in the form of Non-equivalent Control Group Design. Measurement of students' creative thinking ability used questionnaire data and observation sheets, in which data analysis techniques in questionnaires used nonparametric statistical tests namely Mann-Whitney test and observation sheet data used the score of observation sheet reference score. While the measurement of cognitive learning outcomes of students used pre-test and post-test questions in which data analysis techniques used nonparametric statistical tests namely Mann-Whitney test. Statistical test resulted on the creative thinking skills and cognitive learning outcomes of students obtained the significance level (2-tailed) of 0.049 and 0.044 (both are <0.05). This showed that the use of Styrobon learning media influenced creative thinking skill and cognitive learning outcomes of the students.